ChemInform Abstract: New Vistas in the Molecular Chemistry of Thorium: Low Oxidation State Complexes. Issue 26 (June 2016) - Ortu, Fabrizio; Formanuik, Alasdair; Innes, James R.; Mills, David P.
Abstract: Review: 95 refs.